Covert warriors - Griffin, W. E. B.; Butterworth, William E. (New York : G.P. Putnam's Sons, 2011)
When a hostile Third World country begins to receive military training and nuclear technology from foreign nations, Charley Castillo and his team investigate only to be abandoned by the U.S. government and placed on hit lists throughout the world.
"A presidential agent novel"--Jkt. cover.
Keywords: United States. -- Army. -- Delta Force; Castillo, Charley (Fictitious character); Undercover operations; International relations; Spy stories; Suspense fiction; Thrillers